Comparação dos limiares audiométricos obtidos com diferentes estímulos em sujeitos com perdas auditivas com e sem a presença de zumbido - Fratti, Roberta Robba Asola (2009)
Introduction: Despite technological advances currently available, the audiometric test tonal still represents the only test that evaluates the hearing in a range of frequencies. Due to cases of incompatibility of results in clinical practice is essential to conduct research using different stimuli during the tests. Objective: To compare PTA thresholds gotten with the warble and narrow band stimuli in subjects with sensorio-neural hearing loss, without and with tinnitus. Method: The audiometric thresholds by air conduction with the stimulus warble and narrow band were researched in the frequencies 250 to 8000Hz in both ears in three groups: subjects with normal hearing, with hearing loss and without tinnitus and with hearing loss and tinnitus. Results: The results demonstrated meaningful statistic differences between warble and narrow band in all of groups. In the comparative analysis, the differences had been higher, with significance statistics, in the groups with hearing loss when compared with the subjects with normal hearing, independently of the tinnitus. Conclusion: the use of different stimulus in the audiometric evaluation can represent an important strategy for attainment of trustworth thresholds, mainly in subjects with hearing losses